Mechanism of a meteorological tsunami reaching the Japanese coast caused by Lamb and Pekeris waves generated by the 2022 Tonga eruption. (February 2023) - Suzuki, Tatsuo; Nakano, Masuo; Watanabe, Shingo; Tatebe, Hiroaki; Takano, Yuki
Abstract: Tide gauge data indicated that ocean waves were generated by the eruption of the Hunga Tonga-Hunga Ha'apai volcano on January 15, 2022. These high-amplitude waves reached the Japanese coast earlier than expected for free ocean waves. These fluctuations in sea level were reasonably reproduced by an ocean model, with realistic bottom topography forced by sea-level pressure perturbations well reproduced by atmospheric general circulation models. While early arrival times are associated with atmospheric Lamb waves, the amplitude of the sea level changes cannot be fully explained by the resonance mechanism associated with sea-level pressure fluctuations of Lamb and Pekeris waves alone. Rather, resonance due to atmospheric waves in conjunction with the amplification effects caused by a steep continental slope is required in order to reproduce sea level fluctuations along the Japanese coast. In particular, the deep Northwest Pacific Basin to the east of Japan is important for strengthening the amplitude of the meteorological tsunami. Highlights: Sea level fluctuations due to the 2022 volcanic eruption in Tonga was reproduced. Meteorological tsunamis were generated by Lamb and Pekeris waves. Meteorological tsunamis by Pekeris waves are amplified due to Proudman resonance. Meteorological tsunamis are amplified by entering the sharp continental slope.